La formazione e l’aggiornamento dei docenti chimici dell’Università di Palermo: le attività del Progetto Mentore e del TLC-CIMDU - Maggio, Antonella M.; Lombardo, Renato; Chillura Martino, Delia (Chimica nella Scuola, 2024)
The chemists of the University of Palermo are users, but also actors, of teacher training and faculty development. In 2019, the establishment of the TLCCIMDU was the natural evolution of the Project of Mentors for Teaching that began a >few years earlier with the aim to enhance teaching, which appeared to be a secondary activity with respect to research. This contribution describes these experiences by placing them in the broader context of pedagogical changes and technological transformations that affect the teaching-learning relationship in the twenty-first century.